Conflict of interests in biomedicine - Vučković-Dekić Ljiljana (Stomatološki glasnik Srbije, 2004)
All parties in publication enterprise - author, reviewer and editor - have shared interests - to publish good science in good journals. However, in the biomedical arena, the interests (financial or nonfinancial) of each of these parties may conflict with the interests of any of the other parties. Dealing with potential or real conflict of interests that might bias biomedical literature is the important part of both the institution's and the journal's policies. Strict adherence to the highest possible standards of science is the core of ethical regulative of the profession - code of ethics called Good scientific Practice.